BIOLOGICAL STUDIES OF Taenia Saginata METACESTODA DEVELOPMENT IN BALI CATTLE - Dharmawan, Nyoman Sadra; Dwinata, I Made; Swastika, Kadek; Damriyasa, I Made; Oka, Ida Bagus Made; Agustina, Kadek Karang (Buletin Veteriner Udayana; Vol. 8 No. 1 Pebruari 2016, 2016)
The biological studies of Taenia saginata metacestoda development have been conducted in Bali cattle. Two Bali cattle were used as the samples; each was infected by 500.000 T. saginata eggs.  Cattle I and II were slaughtered and examined for the presence of T. saginata metacestodas,103 and 131 days post infection, respectively. All visceral organs and skeletal muscles were thoroughly inspected; incisions and inspection were done following the routine meat inspection.  In cattle I, was observed 534 metacestodas in the skeletal muscles, heart, and diaphragm.  The metacestodas had the form an oval bladder measuring around 3 x 2 mm. While, in cattle II was observed 2,249 metacestodas in the skeletal muscles, heart, diaphragm, and tongue measuring around 4 x 3 mm.  The finding of the present study may indicate that in Bali cattle the oncospheres of T. saginata might reach its optimal development (in to T. saginata metacestoda) in four months post infection.
Keywords: bali cattle, T. saginata eggs, T. saginata metacestoda